Roman Egypt a history - Bagnall, Roger S. 1947-; Haggag, Mona ca. 20./21. Jh; Hickey, T. M. 1967-; El-Maghrabi, Mohamed Gaber; Papaconstantinou, Arietta; Thompson, Dorothy J. 1939- (Cambridge University Press, 2021)
"As Ruler of the Two Lands, Egypt's pharaoh wore the double pschent crown: the red crown of Lower Egypt, in the north, surrounding the white crown of Upper Egypt, in the south. Personified in the ruler, this union remained a central ideal throughout Egyptian history. The unity of Upper and Lower Egypt, also symbolized in the knot tied between papyrus and reed, was long seen as key to Egypt's success. (Fig. 1.1.1) In practice, however, the country was diverse in many ways, with an ongoing struggle between the central ideologies of unity and uniformity and the realities on the ground. Egypt was a self-consciously distinctive culture that also constantly received and absorbed immigrants from many countries into its society"--
Keywords: Römerzeit; Ägypten -- Altertum; Egypt / History / 30 B.C.-640 A.D.; Romans / Egypt; HISTORY / Ancient / General; Romans; Egypt; 30 B.C.-640 A.D.; History